Synthesis of fructooligosaccharides from sucrose using inulinase from Kluyveromyces marxianus - Santos, Andrelina M. P. (Array, 2007)
Fructooligosaccharides (FOS) from sucrose, new alternative sweeteners with functional properties, also called soluble fibers, have a number of desirable characteristics such as low calories, no cariogenicity, and safety for diabetics and Bifidus stimulating factor. Fructooligosaccharides are also known as prebiotics, since they stimulate probiotic organisms. The production, as well as the application of food-grade fructooligosaccharides, has increased rapidly during last years. In this work, experimental factorial design has been applied to optimize the fructooligosaccharide synthesis conditions by inulinase from Kluyveromyces marxianus var. bulgaricus. The studied variables were: temperature, pH, sucrose and enzyme concentrations. According to the results, only temperature and sucrose concentrations have shown to be significant parameters. The syntheses of the fructooligosaccharides were carried out on stirred reactor and packed bed reactors, using free and immobilized enzymes, with the best conditions obtained from the experimental design. It has been shown that there is no significant difference between these processes. The final sugar concentrations can be tailor made by varying residence time in the reactor to cope with the different standard needs in food industries. A typical solution product consists of a mixture of fructose (155 g/L), glucose (155 g/L), sucrose (132 g/L) and fructooligosaccharides (50 g/L)